2022
DOI: 10.1097/coc.0000000000000918
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Primary Gallbladder Cancer Incidence and Incidence-based Mortality in the United States, 1973 to 2015

Abstract: Objectives: Primary gallbladder cancer (GBC) is the most common biliary tract cancer with poor survival despite aggressive treatment. This study aimed to investigate the trends of GBC incidence and incidencebased mortality (IBM) over the last 4 decades.Materials and Methods: GBC cases diagnosed between 1973 and 2015 were retrieved from the Surveillance, Epidemiology, and End Results (SEER) database. Incidence rates, IBM rates, and annual percent changes (APCs) were calculated and stratified according to popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…[34] In GBC patients, overall age-adjusted IBM rate increased from 2000 to 2020, but had plateaued since 2002 (APC = 0.14) compared to 2000 to 2002 (APC = 36.59*). [35] While in patients with cholangiocarcinoma (APC = 44.89*) or pancreatic cancer (APC = 27.79*), overall age-adjusted IBM rate had sheerly increased since 2002, which could partly explained by the increases in the prevalence of risk factors. [10,36] The strengths of our analysis were prominent, including the largest cohort in SEER database, long-term follow-up time and population-based settings.…”
Section: Discussionmentioning
confidence: 99%
“…[34] In GBC patients, overall age-adjusted IBM rate increased from 2000 to 2020, but had plateaued since 2002 (APC = 0.14) compared to 2000 to 2002 (APC = 36.59*). [35] While in patients with cholangiocarcinoma (APC = 44.89*) or pancreatic cancer (APC = 27.79*), overall age-adjusted IBM rate had sheerly increased since 2002, which could partly explained by the increases in the prevalence of risk factors. [10,36] The strengths of our analysis were prominent, including the largest cohort in SEER database, long-term follow-up time and population-based settings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on the Surveillance Epidemiology and End Results (SEER) database have shown a signi cant decrease in the incidence of GBC in the United States over the past 40 years, followed by a stable trend. Incidence-based mortality (IBM) has also experienced an average annual decrease of 1.69%, which may be related to advancements in surgical techniques and adjuvant and neoadjuvant therapies 7,8 . However, an increase in the incidence of GBC has been observed in the population aged < 45 years 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Gallbladder cancer (GBC) is the most common tumor of biliary tract and the sixth most common malignant tumor of digestive system 1 .…”
Section: Introductionmentioning
confidence: 99%